GRANOLA BAR YANG DIFORTIFIKASI DENGAN PROTEIN DAGING KERANG SEBAGAI SNACK SEHAT BAGI ANAK BERKEBUTUHAN KHUSUS - Sata Yoshida Srie Rahayu; Tri Aminingsih; Yulianita . (Ekologia: Jurnal Ilmiah Ilmu Dasar dan Lingkungan Hidup, 2018)
Flour of Anodonta woodiana meat may be added in the manufacture of food products such as granola bar. The aim of addition is to increase the nutritional value on snacks needed by children with special needs through fortification. This research method was done by making products granola bar in three formulas: without the addition of shells flour, the addition of 2.8 gram, and 5.6 gram. Granola bar were made for consumption by children (7-9 years old) and teenager (10-18 years old). Tests performed included organoleptic test. The results of organoleptic test between three formulas of produced granola bar have different characteristics in flavor parameter. The results of the analysis of parameters of color, aroma, and flavor tested by analysis of variance software showed that the most preferred formula is the second formula with the addition 2.8 gram of mussel meat flour. This granola bar snack is a healthy snack that is safe for consumption by children with special needs, because it is made from ingredients that do not contain flavorings, dyes and artificial preservatives.